Natural variation in the plant polyadenylation complex - Zhou, Lichun; Li, Kai; Hunt, Arthur G. (Frontiers in Plant Science, 2024)
Messenger RNA polyadenylation, the process wherein the primary RNA polymerase II transcript is cleaved and a poly(A) tract added, is a key step in the expression of genes in plants. Moreover, it is a point at which gene expression may be regulated by determining the functionality of the mature mRNA. Polyadenylation is mediated by a complex (the polyadenylation complex, or PAC) that consists of between 15 and 20 subunits. While the general functioning of these subunits may be inferred by extending paradigms established in well-developed eukaryotic models, much remains to be learned about the roles of individual subunits in the regulation of polyadenylation in plants. To gain further insight into this, we conducted a survey of variability in the plant PAC. For this, we drew upon a database of naturally-occurring variation in numerous geographic isolates of Arabidopsis thaliana. For a subset of genes encoding PAC subunits, the patterns of variability included the occurrence of premature stop codons in some Arabidopsis accessions. These and other observations lead us to conclude that some genes purported to encode PAC subunits in Arabidopsis are actually pseudogenes, and that others may encode proteins with dispensable functions in the plant. Many subunits of the PAC showed patterns of variability that were consistent with their roles as essential proteins in the cell. Several other PAC subunits exhibit patterns of variability consistent with selection for new or altered function. We propose that these latter subunits participate in regulatory interactions important for differential usage of poly(A) sites.